IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE PAIR CHECK DALAM PEMBELAJARAN MATEMATIKA SISWA KELAS XI IPA 5 SMA NEGERI 1 WONOMULYO - Nurhidayah Nurhidayah (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2016)
The purpose of this study was to determine the implementation of Cooperative Learning Model Pair Check in Learning Mathematics Grade XI IPA 5 SMA Negeri 1 Wonomulyo with reference to the four aspects of implementation that is keterlaksanaan cooperative learning model pair check, student activities during the learning model is implemented, student learning outcomes before and after implementation, and the students' response to the implementation of the learning model. This research is a pre-experimental research design Only One Group Pretest-Posstest Design. This study uses the class as a research subject is class XI IPA 5 SMA Negeri 1 Wonomulyo by the number of students 36 people. Research was conducted during three meetings. The data collection technique used is to observe the observation sheet keterlaksanaan student activity and learning, achievement test given to students, and a student questionnaire responses to determine the response of students to the implementation of cooperative learning model pair check. The results of the qualitative analysis showed that: (1) adherence to learning successfully, (2) the student's activity during the implementation of cooperative learning model pair check tergoolong active, (3) students' response to the implementation of cooperative learning model pair check classified as positive. The results obtained from the quantitative analysis show that: (1) student learning outcomes prior to the implementation of learning model reaches 0% classical completeness, (2) student learning outcomes after the implementation of learning model reaches 77.78% classical completeness. Based on these results, the implementation of cooperative learning model pair check in learning mathematics students of class XI IPA 5 SMA Negeri 1 Wonomulyo succeed.